Strangulated Femoral Hernia With Perforated Jejunal Pseudodiverticula : a Case Report - Ekasaputra, Vito (Sains Medika: Jurnal Kedokteran dan Kesehatan, 2018)
Introduction: Sixty percent of femoral hernias are characterized by incarceration and strangulation. Jejunal pseudo diverticulum are rare and usually asymptomatic. It may cause chronic obstruction of small bowel and can lead to an acute perforation.Case presentation: An 85 – year – old woman presenting with 1 week history of generalized abdominal pain, with episodes of vomiting, fever, and history of 6 months of reponible femoral hernia and 2 weeks strangulated of femoral hernia. An abdominal X-ray displayed multiple dilated loops of the small bowel, coil spring sign and intra peritoneal free air. This patient underwent a laparotomy and hernioraphy, which identified single perforated jejunal pseudo diverticulum 50 cm from ligamentum of treitz orally from strangulated of ileal on femoral hernia site, and associated fecal contamination. The management for this case was perforation repaired with diverticulectomy, simple closure, and extensive washout of intraperitoneal cavity. The non tension femoral hernia repair was performed with monofilament, macroporous MESH.Conclusion: chronic intestinal obstruction caused by femoral hernia in the elderly can lead a performed of intestinal pseudo diverticulum and lead to significant morbidity and mortality. This could be suspected in those presenting with cramping abdominal pain and altered bowel habits.Keywords: hernia, femoral, strangulated, pseudo diverticulum, perforated, management